[OP.8C.04] UNTREATED INDIVIDUALS WITH HYPERTENSION EXHIBIT IMPAIREMENTS IN SKELETAL MUSCLE OXYGENATION AND BLUNTED MICROVASCULAR REACTIVITY. (September 2017) - Dipla, K.; Triantafyllou, A.; Gkaliagkousi, E.; Koletsos, N.; Sachpekidis, V.; Papadopoulos, S.; Vrabas, I.; Zafeiridis, A.; Douma, S.
Abstract : Objective: Endothelial cells across the vascular tree exhibit marked phenotypic heterogeneity in structure and function and vary between different organs and blood vessel types. Although endothelial dysfunction has been observed in several microvascular beds in hypertension, the in vivo microvascular endothelial function within the skeletal muscle in hypertension has not been investigated. This study examined, using near-infrared spectroscopy (NIRS) (i) whether differences in micro-vascular reactivity and skeletal muscle oxygenation exist between untreated individuals with hypertension (HYP) and age-, BMI-, and sex-matched uncomplicated normotensive individuals (NORMO) and (ii) whether microvascular function indices at the skeletal muscle level are associated with arterial stiffness and different blood pressure (BP) (office, ambulatory, and central) measurements. Design and method: Ninety individuals (54 HYP and 36 NORMO), aged 44.7 ± 11.1 years underwent physical examination, office and 24h-BP evaluation, augmentation index (AI) and central BP assessment, and a vascular occlusion test during which NIRS (Artinis) continuously monitored changes in muscle oxygenated and deoxygenated hemoglobin, and tissue oxygen saturation (TSI%). The experimental procedure included: a) baseline, b) a 5-min arterial occlusion for assessing the maximal capacity for O2-extraction by skeletal muscles (mitochondrial function), and c) re-oxygenation (slope and magnitude) for assessing micro-vascular reactivity. Results: No differences were observed at resting TSI (%) between groups, however, during occlusion, HYP exhibited a significantly smaller decline in TSI (deoxygenation-magnitude: 24.6 ± 10.9 vs. 33.0 ± 10; p = 0.001) and a slower rate of de-oxygenation (−0.09 ± 0.04 vs. −0.11 ± 0.03; p = 0.006). During reperfusion, HYP exhibited a smaller increase in TSI (reoxygenation-magnitude: 34.9 ± 14.2 vs. 44.4 ± 12.2; p = 0.002) and a slower rate of reoxygenation (1.2 ± 0.6 vs. 1.5 ± 0.6; p = 0.048). HYP had significantly greater AI than NORMO (AIx75: 24.1 ± 13.3 vs. 14.9 ± 12.9, p = 0.001). Muscle oxygenation responses were significantly correlated with central and ambulatory BP measurements (−0.287 to −0.425; p < 0.05). Conclusions: The blunted skeletal muscle TSI responses during arterial occlusion and reperfusion in HYP compared to NORMO indicate that hypertension is characterized by reductions in the maximal capacity for O2-extraction by skeletal muscles and reduced micro-vascular reactivity at this tissue level. Microvascular indices were correlated stronger with central BP measurements and indices of aortic stiffness than visit BP.